Personal resources of adolescents from incomplete families - Kirenko, Janusz; Bochniarz, Agnieszka (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The subject of interest are the issues concerning the personal resources of adolescents from incomplete families in terms of a sense of coherence and self-evaluation, involving Antonovsky’s Orientation to Life Questionnaire and Rosenberg’s Self-Esteem Scale.
Keywords: personal resources of teenager; sense of coherence; positive self-evaluation; incomplete family